(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2024)
Khiyar is an option or right given to buyers and sellers to choose, whether to continue the contract of sale and purchase or cancel it. Islamic law gives the seller and the buyer the right to ensure that both parties are mutually agreeable. The purpose of giving khiyar is to provide benefits to both parties so that no party feels disappointed with the sale and purchase agreement made. From a legal point of view in Malaysia, the optional element in the law relating to buying and selling in Malaysia is seen to have the same principle as the khiyar element. Therefore, this study highlights the previous studies that debate the principle of khiyar that occurs in the contract of sale between Islamic legislation and the laws relating to the sale and purchase practiced in Malaysia. This study is qualitative by using the method of content analysis. The results of the study found that the application of the principles of khiyar majlis and khiyar syarat is seen differently from the implementation found in the Contracts Act 1950. The principles of khiyar ayb and khiyar ru’yah are clearly applied in the Consumer Protection Act 1999 through several of its provisions. In addition, the similarity of the principles of khiyar ru’yah and khiyar ayb is also found in the provisions of the Sale of Goods Act 1957. This shows that the principle of khiyar found in Islamic jurisprudence is applied in Malaysian law, but not comprehensively. Keywords: Khiyar (option), sale and purchase contracts, Islamic law, Contracts Act 1950, Consumer Protection Act 1999, Sale of Goods Act 1957 Full text: PDF